First record of Hemiberlesia cyanophylli (Hemiptera: Coccoidea) on Opuntia ficus-indica in México - Lázaro-Castellanos, Carlos; Vanegas-Rico, Juan Manuel (Journal of the Professional Association for Cactus Development, 2021)
Opuntia ficus-indica is a cactus distributed in more than 30 countries in the word, it is affected by the presence of hemipteran, of which the superfamily Coccoidea stand out, sessile insect, with a hard cover (armored scales) or without it (soft scales). There are other species of coccoids known as armed scales in the country, which are little studied, since they are usually secondary pests in crops. Therefore, the objective of this work is to present the first record of a species of armed scale on O. ficus-indica in Mexico. For this, cladodes of O. ficus-indica were collected and placed in tricot-nylon bags for review in the laboratory, a photographic record was made, sampling adult scales and fixed in 70% ethanol. The specimens were processed with the Hamon and Kosztarab technique and were determined; obtaining an identification of Hemiberlesia cyanophylli (Signoret) that can occupy up to 86% of the cladode surface.